+0  
 
0
174
1
avatar

https://latex.artofproblemsolving.com/c/b/1/cb111da0c0b3bb7356acf6ba2e82cc76465d96a3.png

Guest Dec 29, 2017
 #1
avatar+91027 
+2

(r + 3)  / ( r - 2)   =  (r - 1)  / ( r + 1)      cross-multiply

 

(r + 3) ( r + 1)  =  (r - 2) (r - 1)     simplify

 

r^2 + 4r  +  3   =   r^2 - 3r  +  2         subtract r^2 from both sides

 

4r + 3   =    -3r  +  2           add 3r to both sides, subtract 3 from both sides

 

7r  =  - 1       divide both sides by 7

 

r  =  - 1/7

 

 

cool cool cool

CPhill  Dec 29, 2017

38 Online Users

avatar
avatar

New Privacy Policy

We use cookies to personalise content and advertisements and to analyse access to our website. Furthermore, our partners for online advertising receive information about your use of our website.
For more information: our cookie policy and privacy policy.